The Effectiveness of Reading Aloud Strategy in Concerning Students' Reading Skills - Nurlaily Sofyan; Jusmin HJ Wahid; Nirwan H Idris (Faculty of Culture, Management, and Business Universitas Pendidikan Mandalika (UNDIKMA), 2021)
Reading Aloud strategy used in the teaching reading skills, which means the teachers and students pronounced the word loudly in front of the class to get the information. The strategy is rewarding for students to understand the reading texts. Then, the researchers used a reading test as an instrument to know the students' competence in reading skills. This research used Quasi-Experimental Design. Â The result was proved that the score in the experimental class was 61 with a standard deviation was 8.20 and the post-test score was 69.1 with a standard deviation was 8.22 then the score of pre-test in the control class was 56.5 with a standard deviation was 8.53 and post-test was 60.40 with standard deviation was 9. 68. The results achieved from both tests were different. Next, the t-test score both in class was 0, 00. It means that the hypothesis is accepted, it concluded that the implementation of the reading aloud strategy can improve students' reading skills competence.